Distributed hierarchical consensus algorithm for economic dispatch in smart grid. Issue 24 (13th November 2019) - Wu, Xiaopeng; Sun, Yonghui; Wei, Zhinong; Sun, Guoqiang
Abstract : In this study, a distributed hierarchical consensus algorithm is proposed to solve the economic dispatch problem in smart grid. In the proposed hierarchical control strategy, the upper level is the leader level, which contains the feedback elements of power difference mismatch and plays a dominant role in the whole algorithm. The lower level is the follower level, which receives information from the leader level and realises self‐adjustment based on the received information. Besides, the constraint conditions of generator nodes are considered to ensure that all of the generator nodes could operate within their limitations. With the increase of the number of leader nodes, the high convergence rate could be illustrated by the comparison between single‐leader node and multi‐leader nodes. Finally, simulation results based on 5‐node network topology and IEEE‐57 bus systems are presented to verify the validity of the proposed algorithm, respectively.